Genome-Wide Metabolic And Evolutionary Analysis Of Paenibacillus Polymyxa Atcc 15970 - Sim , Kee Shin (2015)

(untitled)
Paenibacillus polymyxa ATCC 15970 merupakan bakteria Gram positif hidup bebas dan berkupayaan untuk mengikat nitrogen. Bakteria ini menggalakkan pertumbuhan pokok, penghasilan sebatian antimicrobial dan perembesan enzim hidrolisis. Teknologi penjujukan generasi terkini telah digunakan untuk penjujukan genom bakteria : Roche 454 FLX, Hiseq2000 Illumina Solexa dan Pacbio RS II CLR. Draf genome telah dihimpun dalam tige bersaiz jumlah 6,202,583 bp dengan purata kandungan GC sebanyak 45.6 %. Anotasi genom meramalkan kewujudan 5342 gen pengekodan protein. Genom ini telah mendedahkan satu operon pengikat nitrogen yang disusun sebagai nifBHDKENXV dan hesA. Analisis pembinaan semula metabolic menunjukkan Paenibacillus polymyxa ATCC 15970 mempunyai gen-gen untuk biosintesis lanthionine (metabolit sekunder), hormon pertumbuhan pokok, butanol dan metabolism glikogen. Penyelidikan genom bandingan menunujukkan persamaan yang tinggi dengan genom Paenibacillus polymyxa (strains E681, SC2, M1, CR1, ATCC12321), Paenibacillus durus, Paenibacillus macerans and Paenibacillus terrae HPL-003. Spesies ini meramalkan sebanyak 7 bacteria virus dan 6 CRISPR lokus dengan saiz antara 23 hingga 45 bp. Paenibacillus polymyxa ATCC 15970 is a Gram positive free-living nitrogen fixing bacterium known for its ability to promote plant growth, production of antimicrobial compounds and secretion of hydrolytic enzymes. Genome sequencing of this bacterium was performed using next generation sequencing technology: Roche 454 FLX, Hiseq2000 Illumina Solexa and Pacbio RS II CLR. The draft genome assembled into 3 contig with total bases of 6,202,583 bp with a mean GC content of 45.6%. Genome annotation predicted a total of 5342 protein-coding genes. The genome revealed a single nitrogen fixation operon arranged as nifBHDKENXV and hesA. A metabolic reconstruction analysis indicated that P. polymyxa ATCC 15970 has the genes for the biosynthesis of lanthionine (a secondary metabolite), plant growth hormones, butanol and glycogen metabolism. A comparative whole genome investigation demonstrated high similarity among the genomes of P. polymyxa (strains E681, SC2, M1, CR1, ATCC12321), P. durus, P. macerans and P. terrae HPL-003. The analysis was result a questionable phage out of 7 predicted regions. This species possess also 6 CRISPR loci with size ranging from 23 to 45 bp.